Assessment of treatment efficacy and tolerability in patients with epilepsy: Materials of the meeting of the Central Federal District Neurologists-Epileptologists Expert Council. - N.A. Ermolenko; I.G. Rudakova; G.V. Kalmykova; Yu.A. Kornukova; O.M. Mihailova; G.V. Piskovatskaya; K.V. Tyagunova; L.V. Fedorova; A.A. Gelazhis (LLC "MEDIAFORMAT", 2023)
A meeting of the Central Federal District Neurologists-Epileptologists Expert Council dedicated to the issue of antiepileptic therapy in the CFD regions relative to global data and Russian guidelines was held on December 10, 2022. The priority issues of selecting initial therapy, tactics of patient management considering clinical, gender-related and social features in different age groups were discussed during the meeting. The paper reports conclusions of the meeting of the working group of the CFD experts in neurology and epileptology . The results obtained are the reason to revise the treatment tactics and the guidelines on introduction of new approaches to treatment of patients with epilepsy.